If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50x + -60x + 10 = 0 Reorder the terms: 10 + 50x + -60x = 0 Combine like terms: 50x + -60x = -10x 10 + -10x = 0 Solving 10 + -10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -10x = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -10x = 0 + -10 -10x = 0 + -10 Combine like terms: 0 + -10 = -10 -10x = -10 Divide each side by '-10'. x = 1 Simplifying x = 1
| -2(x+1)-6=(6x-2)+3 | | 0=6-2y | | 20x+30y+50z=240 | | 14-l=-46 | | 8c+-15=-47 | | 9r-34=29 | | 3a-15+4-2a=-17 | | x+4+2x+2+3x+10=18 | | 6x-2(x-6)=4(x+1)+2 | | 9*(3+4)= | | 1.5x+3y-z=-8 | | x-x*0.1=86.96 | | -5(1)=8+4m | | x(5+x)=(x*x)+3x+1 | | 12q-4=32 | | 2(3x-4)+5-4x=11 | | 24x+1.8-x+3=16-1 | | 16x=.6x | | 0.8(x-5)=0.4x-20 | | -Rx+5y=-T | | 7x+-5=4x+4 | | 24x+1*8-x+3=16-1 | | f(x)=x(x+1)(x-6) | | -5(0)=8+4m | | (M+3)(m-4)= | | 56+12x=8+8x | | D=2abc | | 1.5r+15=45r | | -3X+10+4X=13 | | 2ax=10a-3ax | | 8y+8=7y-12 | | 4t-2=33-3y |